Medical Informatics Platform (MIP): A Pilot Study Across Clinical Italian Cohorts - Redolfi, Alberto; De Francesco, Silvia; Palesi, Fulvia; Galluzzi, Samantha; Muscio, Cristina; Castellazzi, Gloria; Tiraboschi, Pietro; Savini, Giovanni; Nigri, Anna; Bottini, Gabriella; Bruzzone, Maria Grazia; Ramusino, Matteo Cotta; et al. (Frontiers in Neurology, 2020)
Please refer to the new manuscript attached.